(untitled) (Comprehensive Journal of Science, 2025)
Reinforced concrete slabs are one of the basic structural elements, playing a key role in transferring loads and providing lateral stiffness to concrete buildings. These slabs often contain openings to service architectural, mechanical, and electrical requirements, which affect the behavior of the structure under seismic loads. This research aims to study the effect of openings in slabs on the nonlinear behavior of a concrete tower using pushover analysis and comparison of capacity curves. The mechanism of this study consisted of data for a cylindrical tower previously designed by (NODUS Engineers Consulting CO.LTD.) the Turkish engineering consulting office NODUS, known as the Hotel Tower, consisting of 32 floors. Openings were made in some of the slabs. A nonlinear modeling approach was implemented using the finite element method for both the slabs and walls. A comparative pushover analysis was then conducted to compare the results at the performance point, comparing slabs containing openings with slabs without openings. The results of the study showed that the effect of openings on displacement at the performance point was limited, with slight differences in shear strength. However, slabs with openings affected the distribution of moments, shear, and settlement locally. This indicates that the shear walls resist most of the lateral forces; therefore, the slabs, even with openings, do not lead to the collapse of the building. This highlights the importance of considering these openings in the design of high-rise buildings to ensure optimal performance and structural safety